2006
DOI: 10.1029/2005jb003961
|View full text |Cite
|
Sign up to set email alerts
|

Spatial correlation of aftershock locations and on‐fault main shock properties

Abstract: [1] We quantify the correlation between spatial patterns of aftershock hypocenter locations and the distribution of coseismic slip and stress drop on a main shock fault plane using two nonstandard statistical tests. Test T 1 evaluates if aftershock hypocenters are located in low-slip regions (hypothesis H 1 ), test T 2 evaluates if aftershock hypocenters occur in regions of increased shear stress (hypothesis H 2 ). In the tests, we seek to reject the null hypotheses H 0 : Aftershock hypocenters are not correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
46
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 54 publications
4
46
1
Order By: Relevance
“…Using finite-fault rupture-model parameters, several authors studied the dynamics of the rupture process and associated ground motion of past earthquakes (e.g., Ide and Takeo, 1997;Zhang et al, 2003;Tinti et al, 2005Tinti et al, , 2009Mai et al, 2006;Causse et al, 2013). Other studies examined stress change on the fault (Ripperger and Mai, 2004), its relation to aftershock occurrence (Woessner et al, 2006) and effects on stress triggering (e.g., Stein, 2003), and postseismic processes (e.g., Ergintav et al, 2009). Detailed information on the kinematic rupture process also helps to shed light on the physics of rupture nucleation, propagation, and arrest (e.g., Mai et al, 2005;Gabriel et al, 2012) and allows the development of relations between slip asperities, temporal rupture properties, and geometrical source effects.…”
Section: Introductionmentioning
confidence: 99%
“…Using finite-fault rupture-model parameters, several authors studied the dynamics of the rupture process and associated ground motion of past earthquakes (e.g., Ide and Takeo, 1997;Zhang et al, 2003;Tinti et al, 2005Tinti et al, , 2009Mai et al, 2006;Causse et al, 2013). Other studies examined stress change on the fault (Ripperger and Mai, 2004), its relation to aftershock occurrence (Woessner et al, 2006) and effects on stress triggering (e.g., Stein, 2003), and postseismic processes (e.g., Ergintav et al, 2009). Detailed information on the kinematic rupture process also helps to shed light on the physics of rupture nucleation, propagation, and arrest (e.g., Mai et al, 2005;Gabriel et al, 2012) and allows the development of relations between slip asperities, temporal rupture properties, and geometrical source effects.…”
Section: Introductionmentioning
confidence: 99%
“…Luo and Ampuero (2017) performed a thorough stability analysis of an infinite frictionally heterogeneous fault. Yabe and Ide (2018;hereafter YI18) reproduced aftershocks within the mainshock rupture area (e.g., Beroza and Zoback 1993;Woessner et al 2006) by considering the partial rupture of a frictionally heterogeneous fault. Dublanchet et al (2013) and YI18 reported foreshocks before the mainshock, though no previous study has investigated the causes of variations in foreshock activity.…”
Section: Introductionmentioning
confidence: 99%
“…(2) Mc determines the minimum magnitude of a complete seismicity catalog, and is directly linked to the input data of the artificial neural network (ANN) technique for modeling and forecasting the earthquake energy release. A number of studies have shown that Mc may change with time (Hutton et al 2010;Michael 2014;Woessner et al 2006;Woessner and Wiemer 2005). In particular, Michael (2014) shown that the values of Mc of ISC-GEM earthquake catalog significantly vary with different time periods.…”
mentioning
confidence: 99%